ENGLISH TRAINING WITH DRILLS AND REPETITION FOR SIMPURSIA VILLAGE CORAL CADETS - Satriani Satriani; Muhammad Hasbi (Perkumpulan Dosen Muslim Indonesia, 2021)
The service team provides solutions based on the results of an analysis of the situation and problems faced by partners to increase opportunities for youth members to be immediately accepted to work after completing their education at vocational high schools. In terms of the solution's form, namely training and mentoring for youth members to practice spoken English using the drilling and repetition method, the results obtained at the end of this service were: (1) positive and enthusiastic response from members of the youth organization; (2) increased awareness of the importance of spoken English proficiency; (3) willingness to take risks in order to participate; (4) increased spoken English vocabulary, grammar, and pronunciation; (5) greater access to recorded voices of foreign speakers; and (6) more opportunities to practice speaking English in dynamic and enjoyable (but not monotonous) settings. (7) the availability of foreign speakers' voices in the form of mp3 recordings; (8) in their spare time, members of the youth organization are encouraged to listen to foreign speakers' voices, imitate them, and practice independently; and (9) after the training and mentoring is completed, the future availability of online sites for accessing and downloading learning media files.